Targeting Liver Xor by GalNAc-siRNA Is an Effective Strategy for Hyperuricemia Therapy - Huiyan Sun; Xinxia Wang; Yongqiang Li; Yingzhi Shen; Lin Zhang; Yingjie Xu; Junling Liu; Xuemei Fan (MDPI AG, 2024)
Hyperuricemia, i.e., increased plasma uric acid concentration, is a common problem in clinical practice, leading to gout or nephrolithiasis, and is associated with other disorders, such as metabolic syndrome, cardiovascular disease, and chronic renal disease. Xanthine oxidoreductase (XOR) is a critical rate-limiting enzyme involved in uric acid synthesis and a promising target for hyperuricemia therapy. However, XOR inhibitors currently face clinical problems such as a short half-life and side effects. Here, we found that specifically targeting liver Xor with GalNAc-siRNAs had a good therapeutic effect on hyperuricemia. First, siRNAs were designed to target various sites in the homologous region between Homo sapiens and Mus musculus Xor mRNA and were screened in primary mouse hepatocytes. Then, the siRNAs were modified to increase their stability in vivo and conjugated with GalNAc for liver-specific delivery. The effects of GalNAc-siRNAs were evaluated in three hyperuricemia mouse models, including potassium oxonate and hypoxanthine administration in WT and humanized XDH mice and Uox knockout mice. Febuxostat, a specific XOR inhibitor used for hyperuricemia treatment, was used as a positive control. Targeting liver Xor with GalNAc-siRNAs by subcutaneous administration reduced plasma uric acid levels, uric acid accumulation in the kidney, renal inflammation, and fibrosis, thereby alleviating kidney damage in hyperuricemia mouse models without hepatoxicity. The results demonstrated that targeting liver Xor with GalNAc-siRNAs was a promising strategy for hyperuricemia therapy.